Segera Bergerak sebagai Cara Menyembuhkan Cedera setelah Operasi SC - Muji Lestari; Fahry Amal (Politeknik Kesehatan Kemenkes Mamuju, 2020)
One marker of the level of Public Health in a country, including Indonesia, is the Mortality Rate (MMR) and Infant Mortality Rate (IMR). Maternal death can be caused by many factors, one of which is labor, specifically labor by Caesarean Sectio (SC). Ironically, childbirth by means of SC is now more and more chosen compared to normal (pervaginam) delivery, especially in big cities. Childbirth by means of SC, in addition to increasing the risk of death can also be one cause of infection if treatment is done incorrectly. Caesarean section seams have a risk of infection during the healing process, if not handled properly and correctly will cause many problems, both immediate and problems that arise later. Immediately moving is a way to speed healing, if this is not done it can cause an increase in body temperature due to a poor uterus so that the rest of the blood cannot be removed and causes infection. The aim of this research was to find out the impact of early mobilization in post partum mothers with sectio caesarea (SC) to the post partum SC wound healing process. Draft study was observasional with cross sectional design. The patients who gave birth to SC in the postpartum room of Abepura General Hospital in May 2017 totaling 33 people were the population in this research. The sample in this research are all postpartum sectio caesarean in the postpartum room of Abepura General Hospital in May 2017 totaling 33 people. The sampling technique is accidental sampling. Data was analyzed using chi square statistical tests. There are 11 respondents who do not conduct early mobilization and 22 respondents who die early mobilization. The results indicate that there is relation among early mobilization with recovery rate, Î±=0,000 <0,05. Early Mobilization is a way to heal an injury after SC.